In Search of Coincident and Leading Indicators of Economic Activity in Argentina - Simone, Alejandro (IMF Working Papers; Working Paper, 2001)
Time series on economic activity in developing countries, in particular real GDP, are reported with important lags. Therefore, it is useful to construct indicators that coincide or lead the actual direction and level of economic activity. A general methodology to construct these indicators is proposed and adapted for Argentina. Three coincident indicators could be constructed, but no reliable leading indicator could be found. From an econometric standpoint, the coincident indicators produce satisfactory point estimates of real GDP. The series that enter the indicator are broadly consistent with what many economists believe is the main source of real GDP fluctuations in Argentina: shocks to the capital account of the balance of payments. This enhances the confidence in the econometric results.